Fishbone-Associated Actinomycosis of the Anterior Cervical Space: A Diagnostic Dilemma - Sang Kwon Lee; Mi Jeong Kim; Sun Young Kwon (Case Reports in Medicine)
We report the imaging and pathologic findings of fishbone-associated actinomycosis of the anterior cervical space in a 57-year-old man, misdiagnosed preoperatively as a malignancy originating from thyroglossal duct cyst. CT revealed an enhancing mass containing a small abscess pocket and two sharp linear calcifications within it, which infiltrated into the strap muscle. Pathologic examination demonstrated two fishbones within the actinomycotic abscess. Fishbone-associated actinomycosis should be considered when a cervical mass contains sharp linear calcifications.